Utilization of L-cystine as a source of carbon and nitrogen by various fungi - Kunert, J (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 1989)
Thirty fungal species from various taxonomic and ecologic groups were cultivated on two glucose-peptone media enriched with cystine (3 mmol/l). Nineteen species showed certain ability to utilize cystine not only as a source of sulfur but that of carbon and nitrogen as well; six species utilized cystine completely. Excess sulfur was excreted after oxidation in the form of inorganic sulfate and/or sulfite back into the medium. Cystine metabolization was on average more rapid and complete on the medium with higher peptone content and better growth. When compared with keratinolytic fungi studied previously, the present set of fungi showed a lower tendency to cystine utilization and comprised species not utilizing this amino acid at all.
Keywords: peptony; síra; Fungi; Cystine; cystin; kultivační média; uhlík; Carbon; glukosa; houby; Nitrogen; dusík; Glucose; Culture Media; Peptones; Sulfur